The Effect of Gadget use Elementary School-Aged Students at SDN 2 Momun, Buol Regency - Ahmad, Lianita; Salham, Munir; Nur, Andi Reza Alief Chairin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2021)
Gadgets are electronic devices that are easy to carry anywhere for communication or information purposes. Nowadays, through gadgets people can communicate face to face via video calls so that gadgets are used by many people ranging from parents to children. The type of research used is descriptive qualitative. The data collection techniques are observation, interview, and documentation. The number of informants is 9 consisted of 1 teacher, 4 students, and 4 parents. The results show that the use of gadgets on elementary school students at SDN 2 Momunu has positive and negative impacts. The positive impact is to make it easier for students to find various information in learning media, increase students' intelligence, and increase self-confidence. The negative impact is a lack of concentration on students, laziness, and health problems. In this research, it is suggested that parents and schools pay more attention and be more assertive towards their children in using gadgets so that children know the limitations of using gadgets.